Revision of the genus Gelastissus Kirkaldy (Hemiptera, Fulgoroidea, Caliscelidae) - Gnezdilov, Vladimir M. (Zootaxa, 2008)
The genus Gelastissus Kirkaldy, 1906 is revised. Conocaliscelis Matsumura, 1916 is placed in synonymy under Gelastissus Kirkaldy, 1906. Gelastissus histrionicus Kirkaldy, 1906 is placed in synonymy under G. albolineatus Kirkaldy, 1906 and Conocaliscelis koshunensis Matsumura, 1916 under C. hokutonis Matsumura, 1916. G. albolineatus is firstly recorded from New Guinea and G. hokutonis from Vietnam.